Author Correction: Genetic Factors and Genotype-Environment Interactions Contribute to Variation in Melanin Production in the Fungal Pathogen Cryptococcus neoformans - Himeshi Samarasinghe (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.